Exploration of Positive Deviance in Prevention of Underweight in the Under-Five: A Qualitative Study on Low-Income Urban Families - Budiono, Irwan; Fauzi, Lukman; Rochmayani, Dewi Sari (UI Scholars Hub, 2024)
Children under the age of five (the under-five) from low-income families are more vulnerable to experience underweight. This nutritional vulnerability is evident in the preliminary study, where 35.1% of the under-five experience underweight, and 28.48% are low-income families. This study aimed to explore Positive Deviance (PD) behaviors in preventing underweight among the under-five. The study applied a qualitative approach with a case study design. Data collection took place in July-August 2022, focusing on low-income families in the Gunung Brintik area. Data were collected through two focus group discussions, seven in-depth interviews, and five key informant interviews. Coding, subtheme, and theme development were facilitated using the ATLAS.ti trial package. Triangulation of the study results yielded four major themes influencing the prevention of underweight in the under-five: interventions by health workers and cadres, community awareness and concern, family support, and maternal nutrition literacy. The identified PD behaviors practiced by the community in the study location have been shown to contribute to the prevention of underweight in the under-five. Strengthening these identified PD behaviors and their implementation in other areas is essential to support efforts to combat underweight in the under-five.